Service Techniques To Improve Volyball GameS - Destriana, Destriana; Destriani, Destriani; Yusfi, Herri (JPI (Jurnal Pendidikan Indonesia), 2020)
The purpose of this research is to produce learning techniques for volleyball service for class IX Junior High School so that by producing new learning techniques, the learning outcomes of student service will be better, this research and development is intended to be a solution to the problem of volleyball game service at junior high school students. This research uses the Research and Development (R&D) method using the ADDIE development procedure (Analyze, Design, Development, Implementation, and Evaluation). Data was collected through documentation, observation, questionnaires and top service assessment tests. Data analysis was carried out descriptively, qualitatively and quantitatively. The product implementation stage was carried out in class IX.2 totaling 32 students and IX 4 totaling 32 students at Junior High School No 1 Palembang using the development results in the form of 8 top service drill learning techniques that had been declared valid. The learning outcomes of student service in the realm of attitudes, knowledge and skills obtained an average of 88.58% of students passed the minimum completeness criteria. Based on these learning outcomes, it can be concluded that 8 top service drill learning techniques are said to be effective in learning to serve volleyball games in junior high school students. The findings in this study are that the 8 drill learning techniques developed for top service can be used as a reference for learning techniques that can improve learning outcomes for volleyball service learning.